ANÁLISE MORFOMÉTRICA DA MICROBACIA DO CÓRREGO DO VANGASSE - PRATÂNIA/SP - Timóteo Rodrigues, Mikael; Manfrin Garcia, Yara; Timóteo Rodrigues, Bruno; Gehring Cardoso, Lincoln (Electronic Journal "Fórum Ambiental da Alta Paulista", 2013)
.